PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN TELEKOMUNIKASI - Tasman H Taher; Robert Fransiska (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
Therefore, the objective of this research was to find out and investigate how intense the effect of Occupational Health and Safety (OHS) on the employee performance about the Palangka Raya branch employees of PT. Telkom is. This research conducted simple random sampling as the sampling technique since the samples were randomly withdrawn from the population without considering the strata of the population. In addition, the size of the sample computed in this research was determined by the Slovin’s formula in which obtained 64 respondents used for the samples as the result. Meanwhile, the research was implemented using the descriptive analysis in quantitative approach with questionnaire as the research data collecting instrument and also simple linear regression analysis technique to assess the effect of the independent variable (X) on the dependent variable (Y) in which regarding to this research, the independent variable (X) is the Occupational Health and Safety (OHS) while the dependent variable (Y) is the employee performance. The tabulation of data in this research was completed using the 19th version of Statistical for Product and Service Solution (SPSS) program. Moreover, the result attained from this research showed that there is a significant and positive effect of Occupational Health and Safety (OHS) on employee performance about the Palangka Raya branch employees of PT. Telkom in view of the fact that the regression coefficient of the independent variable (X) or the Occupational Health and Safety (OHS) that showed 0.461 and F Test resulted in 12.089 with 0.001 significance or less than <0.05 which is higher than table F of 4.00 (significant).